Theoretical Design of Electrostatic Lens Accelerating and Decelerating Operated Under Different Magnification Conditions - Hussein, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper,  design computationl investigation in the field of charged-particle optics with the aid of numerical analysis methods  under the absence of space charge effects. The work has been concentrated on the design of three-electrode  einzel electrostatic  lens accelerating and decelerating operated under different magnification conditions.     The potential field distribution of  lens has been represented by exponential function.  The paraxial-ray equation has been solved for the proposed field to determine the trajectory of charged-particles traversing in the lens.  From The axial  potential distribution and its first and second derivatives, the optical properties such as the focal length and the spherical and chromatic aberration coefficients have been computed, the electrode shape of lens has been determined by using SIMION computer program .     In this research , design electrostatic einzel lens three-electrode accelerating and decelerating L=2mm, 20mm operated under different magnification conditions (zero, infinite, finite). The electrode shape of the electrostatic lens was then determined from the solution of the Laplace's equation. The results showed low values of spherical and chromatic aberrations which are considered as good criteria for good design